Effects of Carbon Fiber on Mechanical Properties of Reactive Powder Concrete - Helmi, Masdar; Alraimi, Ala Ali Qasem (Journal of the Civil Engineering Forum, 2024)
The use of fiber generally might change the mechanical properties of concrete in flexural or compressive strength. Reactive powder concrete (RPC) is one of the ultra-high-performance concrete types that has been applied for some constructions. Carbon fiber, having high strength in tensile, also has the potency to improve the physical characteristics of RPC. The purpose of this study is to evaluate the flexural and compressive performance of RPC, focusing on the interfacial binding of carbon fiber. Flexural and compressive tests used samples with dimensions of 40 x 40 x 160 mm were tested in accordance with BS-EN-196-1:2011, which allows to use one of the two broken pieces from the flexural test as the sample. The microstructure surrounding carbon fiber and paste was qualitatively compared using Scanning Electron Microscopy (SEM) in the secondary electron detector mode. Samples were subjected to static pressure at 8 MPa after 1 hour of pouring and heat curing at 240 °C in a dry oven after demolding. Results show that the presence of carbon fiber increased the flexural strength of RPC by up to 28.85% for samples without treatments and up to 14.32% for samples with both treatments. Although carbon fiber increased toughness by 20% and flexural modulus by 6%, it had no effect on the failure mode after reaching the peak load, which remained brittle. On the other hand, the presence of carbon fiber had little effect on compressive strength. Despite the pressure and heat, curing treatments had no effect on enhancing the adhesion between carbon fiber and cement paste, which was indicated by theundamaged surface of carbon fiber. However, the implementation of both treatments on samples might produce RPC with good mechanical properties in flexure.